Organizacja dynamiczna a zmiany na przykładzie Eurobanku SA we Wrocławiu - Zając, Czesław (The dynamic organization and changes in Eurobank SA, 2006)
The paper presents the issue of changes in the dynamic developing organization from the point of view of the essence and social effects of these changes, and ways of shaping them. They arc described on the basis of the empirical research made by the author in Eurobank SA. The results of this research indicate that rapid and violent productive, structural, organizational and ownership changes lead to the deep changes in the area of human resources and organizational culture. Especially the ownership changes via the acquisitions done by the institutional branch investors - big international corporation, generate the transformation of norms and values and as a result the changes of the behavior and attitudes of employees and managers in acquired companies. This research is also the testimony of the fact, that owners treat business goals and tasks as the priority in the first phase of development of their companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 177-182